Ідентифікація параметрів інтервальних моделей статичних систем методами оптимального планування насичених експериментів - Олійник, Ірина Степанівна (Тернопільський національний економічний університет, 2018)
Дисертаційна робота присвячена розв’язуванню актуального науково-прикладного завдання зниження обчислювальної складності методів параметричної ідентифікації інтервальних моделей статичних систем з гарантованими прогностичними властивостями, за рахунок створення нових методів еліпсоїдного оцінювання множини значень параметрів. Розроблено метод еліпсоїдного оцінювання множини значень параметрів інтервальних моделей статичних систем, в якому, на відміну від існуючих, застосовано ітераційну обчислювальну схему оптимального планування експерименту, що забезпечило зниження обчислювальної складності у порівнянні із відомими методами. Розроблено метод оптимального насиченого планування експериментів у випадку інтервального представлення вихідних змінних моделей статичних систем, який, на відміну від існуючих, ґрунтується на ітераційній обчислювальній процедурі оптимізації прогностичних властивостей інтервальних моделей. Удосконалено метод параметричної ідентифікації інтервальних моделей статичних систем, який побудовано на поєднанні удосконаленого методу редукції інтервальної системи лінійних алгебричних рівнянь та нового розробленого методу еліпсоїдного оцінювання множини значень параметрів інтервальних моделей статичних систем. На основі розроблених у дисертаційному дослідженні методів, із застосуванням створеної програмної системи побудовано інтервальну модель характеристик малої гідроелектростанції та інтервальну модель добової зміни концентрації шкідливих викидів діоксиду азоту, в залежності від інтенсивності транспортних потоків, відносної вологості та температури повітря. адного задания снижения вычислительной сложности методов параметрической идентификации интервальных моделей статических систем с гарантированными прогностическими свойствами, за счет создания новых методов эллипсоидного оценивания множества значений параметров. Разработан метод эллипсоидного оценивания множества значений параметров интервальных моделей статических систем, в котором, в отличие от существующих, применено итерационную вычислительную схему оптимального планирования эксперимента, что обеспечило снижение вычислительной сложности по сравнению с известными методами. Разработан метод оптимального насыщенного планирования экспериментов в случае интервального представления исходных переменных моделей статических систем, который, в отличие от существующих, основывается на итерационной вычислительной процедуре оптимизации прогностических свойств интервальных моделей. Усовершенствован метод параметрической идентификации интервальных моделей статических систем, построенный на сочетании усовершенствованного метода редукции интервальной системы линейных алгебраических уравнений и нового разработанного метода эллипсоидного оценивания множества значений параметров интервальных моделей статических систем. На основе разработанных в диссертационном исследовании методов, с применением созданной программной системы построено интервальную модель характеристик малой гидроэлектростанции и интервальную модель суточного изменения концентрации вредных выбросов диоксида азота, в зависимости от интенсивности транспортных потоков, относительной влажности и температуры воздуха. Dissertation is devoted to solving the actual scientific and applied problem of reducing the computational complexity of the methods of parametric identification of interval models of static systems with guaranteed prognostic properties, by creating new methods of ellipsoid estimation of a set of parameters values. It is analyzed and substantiated that in order to solve problems in conditions of bounded error values. It is expedient to use methods of interval analysis of data. Methods of solving the interval system of linear algebraic equations, in particular methods of interval estimation, ellipsoid estimation and allocation of the "saturated" block by interval system of linear algebraic equations are analyzed, and their defects are established. Based on the results of the analysis of the methods of estimating the area of parameters, the using of the method with localization of interval system of linear algebraic equations solutions in the form of a "saturated" block was substantiated. The method for ellipsoid estimation of the set of parameters values of interval models of static systems is developed, in which, unlike the existing ones, iterative computational scheme of optimal design of the experiment was applied which provided decrease of computational complexity in comparison with known methods. The method of optimal saturated design of experiments in the case of interval representation of output variables of static systems models is developed, which, unlike existing ones, is based on the iterative computational procedure of optimization of predictive properties of interval models. The method of parametric identification of interval models of static systems is improved, which is constructed by combining the advanced ISLAE reduction method and the newly developed method of ellipsoid estimation of the set of parameters values of the interval models of static systems. Based on the methods developed in the dissertation research, with the application of the created software system, an intermediate model of the characteristics of a small hydroelectric power station and an interval model of the daily change in the concentration of harmful emissions of nitrogen dioxide, depending on the traffic intensity, relative humidity and air temperature, were constructed.
Идентификация параметров интервальных моделей статических систем на основе методов оптимального планирования насыщенных экспериментов
Identification of parameters of interval models of static systems based on the methods for optimal design of a saturated experiment
Keywords: «насичений» блок; інтервальна система лінійних алгебричних рівнянь; інтервальна модель; параметрическая идентификация; метод эллипсоидного оценки решений; «насыщенный» блок; интервальная система линейных алгебраических уравнений; интервальная модель; параметрична ідентифікація; метод еліпсоїдного оцінювання розв’язків; parametric identification; method of ellipsoidal estimation of solutions; "saturated" block; interval system of linear algebraic equations; interval model; 519.876.5